Ritual Change and the Distant: Mesoamerican Iconography, Scarlet Macaws, and Great Kivas in the Mimbres Region of Southwestern New Mexico. Issue 1 (January 2014) - Gilman, Patricia A.; Thompson, Marc; Wyckoff, Kristina C.
Abstract: The Mimbres Classic period (A .D. 1000–1130) in southwestern New Mexico was marked by dramatic and complex changes. The use of Great Kivas ended, and macaws and Mesoamerican-inspired iconography appeared. We argue that these events were systematically related and signify observable changes in Mimbres ritual economy. The presence of macaws, images of macaws, and representations of characters and motifs from the Hero Twins saga suggest that ideology accompanied macaws north from the Gulf Coast of Mexico. We recognize and discuss episodes and icons from the saga painted on Mimbres black-on-white bowls and propose that the macaws and narrative reached the Mimbres region through direct acquisition rather than down-the-line trade. This research has significant implications for the importance of long distance travel to faraway places and interaction with distant peoples, Mesoamerican-southwestern United States relationships, changing religious practices in non-hierarchical societies, and the adoption of extrinsic elements into local settings.